Malachite Green Adsorption Behavior of Polyurethane/Chitosan Composite Foam. Issue 1 (January 2016) - Li, X.X.; Li, J.; Cai, L.Y.; Li, T.T.; Liu, X.F.; Li, J.R.
A composite foam of polyurethane/chitosan with chitosan content of 20 wt% was successfully prepared as an adsorbent for the removal of malachite green from aqueous solution, the structures and properties were characterized by scanning electron microscope and Fourier transform infrared spectroscopy. The results showed open cell content of polyurethane/chitosan was more than 95% and open cell structure was intuitive shown by scanning electron microscope images. It was revealed that polyurethane/chitosan exhibiting high efficiency on malachite green adsorption. Fourier transform infrared spectroscopy study showed that possible pathway for malachite green adsorption may include hydrogen bond and acetyl groups. The adsorption isotherms, kinetics and thermodynamics of polyurethane/chitosan for malachite green were studied in detail, and adsorption process followed Langmuir isotherms model rather than pseudo-second-order kinetic model. The activation energy value indicated that the adsorption was mainly physical process.